2019
DOI: 10.2306/scienceasia1513-1874.2019.45.109
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Helicobacter pylori, anti-inflammatory and antioxidant evaluation of crude extracts from Amomum krervanh fruits

Abstract: The aim of the present study was to determine the antibacterial properties against Helicobacter pylori and the anti-inflammatory and antioxidant activities of crude A. krervanh extracts. The minimum inhibitory concentrations (MICs) of ethanolic and aqueous extracts were measured against standard strain H. pylori standard (ATCC 43504) and six clinical isolates by disc diffusion and agar dilution. Anti-inflammatory activities were evaluated by measuring the inhibition of nitric oxide (NO) production in LPS-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…On the other hand, the water and ethanolic extracts did not show the correlation between the inhibitory activity on nitric oxide, TNF-α, and IL-6 productions. The previous investigation by Bhanuz et al [6] revealed that the ethanolic extract of the Amomum Krevanh fruit showed higher anti-inflammatory activities than the water extract in both nitric oxide and interleukin-6 pathways. Additionally, the anti-H. pylori and antioxidant activities of the ethanolic extract were also higher than the water extract.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, the water and ethanolic extracts did not show the correlation between the inhibitory activity on nitric oxide, TNF-α, and IL-6 productions. The previous investigation by Bhanuz et al [6] revealed that the ethanolic extract of the Amomum Krevanh fruit showed higher anti-inflammatory activities than the water extract in both nitric oxide and interleukin-6 pathways. Additionally, the anti-H. pylori and antioxidant activities of the ethanolic extract were also higher than the water extract.…”
Section: Resultsmentioning
confidence: 96%
“…The plates were incubated as previously described for 3 days. The zone of inhibition was calculated by measuring the diameter of the inhibition zone 3 times, and the mean value was taken [6,12].…”
Section: Anti-helicobacter Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that 4b has the highest IC 50 (294.79 ± 1.12 µM), while the lowest is found in 4a (103.28 ± 0.15 µM). Moreover, all samples at a concentration of 15.63 µM were potentially non-toxic, as indicated by cell viability of more than 70% [22]. Therefore, the 15.63 µM concentration of samples that exhibited 70% cell viability against RAW264.7 cell was chosen for the anti-inflammation assay.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…3 (4, 5 dimethyl-2-thiazolyl)-2, 5 diphenyl tetrazolium bromide (MTT) is a yellow chemical substance, which becomes blue formazan when dehydrogenated by mitochondria of living cells [17]. The MTT assay had been applied for assessing cell metabolic activity, cytotoxicity or loss of viable cells [17][18][19]. Vancomycin is a bactericidal agent which kills the susceptible bacterial cells.…”
Section: Introductionmentioning
confidence: 99%